Fossil Bibionidae (Diptera: Bibionomorpha) from the late Oligocene of Bes-Konak, Anatolia, Turkey - Skartveit, John; Nel, André (Zootaxa, 2012)
Three new species of bibionid flies are described from the late Oligocene deposit of Bes-Konak, Anatolia, Turkey: Bibio ana-tolicus sp.n., Bibio nigricosta sp.n. and Penthetria beskonakensis sp.n. These genera are associated with temperate climate,contrasting with the bibionid Oligocene fossils from some other European localities with warmer climates, where the intertropical genus Plecia often predominates.Keywords: Bibio, Penthetria, Cenozoic, palaeoclimatic indicators